Eugenol and carvacrol excite first- and second-order trigeminal neurons and enhance their heat-evoked responses - Klein, Amanda H. (2014)
Eugenol and carvacrol from clove and oregano, respectively, are agonists of the warmth-sensitive transient receptor potential channel TRPV3 and the irritant-sensitive TRPA1. Eugenol and carvacrol induce oral irritation that rapidly desensitizes, accompanied by brief enhancement of innocuous warmth and heat pain in humans. We presently investigated if eugenol and carvacrol activate nociceptive primary afferent and higher-order trigeminal neurons and enhance their heat-evoked responses, using calcium imaging of cultured trigeminal ganglion (TG) and dorsal root ganglion (DRG) neurons, and in vivo single-unit recordings in trigeminal subnucleus caudalis (Vc) of rats. Eugenol and carvacrol activated 20-30% of TG and 7-20% of DRG cells, the majority of which additionally responded to menthol, mustard oil and/or capsaicin. TG cell responses to innocuous (39°) and noxious (42°C) heating were enhanced by eugenol and carvacrol. We identified dorsomedial Vc neurons responsive to noxious heating of the tongue in pentobarbital-anesthetized rats. Eugenol and carvacrol dose-dependently elicited desensitizing responses in 55% and 73% of heat-sensitive units, respectively. Responses to noxious heat were briefly enhanced by eugenol and carvacrol. Many eugenol- and carvacrol-responsive units also responded to menthol, cinnamaldehyde and capsaicin. These data support a peripheral site for eugenol and carvacrol to enhance warmth- and noxious heat-evoked responses of trigeminal neurons, and are consistent with the observation that these agonists briefly enhance warmth and heat pain on the human tongue.